Novel effective bioprocess for optimal CO2 fixation via microalgae-based biomineralization under semi-continuous culture. (November 2022) - Yu, Byung Sun; Yang, Ha Eun; Sirohi, Ranjna; Sim, Sang Jun
Graphical abstract: Highlights: Calcite crystals were generated on the cell surface of Chlorella sp. HS2. Biomineralization minimized culture period by increasing photosynthetic efficiency. Reaction was successful under mildly alkaline pH and mild CaCl2 concentration. Biomass and lipid production were successfully maintained for cultivation period. CO2 removal rate increased considerably, and required area for mitigation decreased. Abstract: In this study, the effects of microalgae-based biomineralization in a semi-continuous process (M-BSP) on biomass productivity and CO2 fixation rate were investigated. M-BSP significantly improved biomass production and CO2 fixation rate at the second stage of induction by sustaining relatively high photosynthetic rate without exposure to toxic substances (e.g., chlorellin) from aging cells using the microalgae Chlorella HS2. In conventional systems, cells do not receive irradiated light evenly, and many cells age and burst because of the long culture period. In contrast, in the M-BSP, the photosynthesis efficiency increases and biomass production is not inhibited because most of the cells can be harvested during shorter culture period. The accumulated biomass production and CO2 fixation rate of the HS2 cells cultured under M-BSP increased by 4.67- (25 ± 1.09 g/L) and 10.9-fold (30.29 ± 1.79 g/L day −1 ), respectively, compared to those cultured without the CaCl2 treatment.